KONSEP PERNIKAHAN LINTAS KEYAKINAN DALAM BERAGAMA PERSPEKTIF AYAT-AYAT AL-QUR’AN DAN HADIST RASUL - Abd. Muiz; Herlin Susantin (Institut Dirosat Islamiyah Al-Amien Prenduan, 2020)
Marriage is the most sacred moment in human life in this world. with the existence of marriage a person has followed one of the traditions taught by the prophet Muhammad Saw. In this contemporary era, the term marriage of different religions has emerged, thus attracting controversy among mslim intellectuals. There are some who disagree and there are also some who disagree. For this reason, this research uses a descriptive qualitative approach using the type of literature study research. The result of this study is that the law of marriage with a religion for a Muslim man with a woman musyrikah the law is haram. Meanwhile, muslim women with muslim women with musyrikah men are also illegitimate.